The Influence of Prisoner Sentence Periods on Family Harmony from the Perspective of Islamic Family Law - Ulham Pratama; Widiya Yul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
Imprisonment for inmates inevitably restricts the fulfillment of their rights and obligations as husbands or wives and as parents. This study aims to examine how the incarceration period of inmates at Class II B Sungai Penuh Detention Center affects their family harmony, and to explore possible solutions that can be offered to inmates to maintain family well-being. This research is qualitative in nature. The respondents consisted of spouses of inmates who were selected purposively. Data were collected through interviews and supported by questionnaire results. The findings show that the incarceration period has a significant effect (P